Sosialiasi Literasi Digital Untuk Meningkatkan Kualitas Belajar Siswa Di Dalam Pembelajaran - Mitra Binariang Lase; Benteng Martua Mahuraja Purba; Yuniarti Yuniarti; Damai Putra Gulo; Sepril Oskar Saroro; Nening Satriani Radja; Frienda Sirait; Delvi Hutapea; Puspa Sarah Renjelina Marpaung; Jelita sitinjak; Bina Monika Br Siringo-ringo; Lastri Samosir; Anita Berutu (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
The development of technology and information has brought all students into the world generation of digital literacy, media technology or digital literacy is developing rapidly, many people are able to create new applications, technological devices that aim to provide convenience for humans. Excessive use of digital can cause problems, especially for students who are still in education, misusing technology can reduce the quality of student learning. The effort that we can do to overcome this problem is by reviving students' thinking concepts in improving the quality of learning by using digital learning media. The purpose of this research is to find out to what extent students are able to utilize technology, what efforts can help students who are addicted to technology. This research was conducted at the Anugerah Tanjungpinang Social Service Foundation Middle School using the face-to-face method from preparation to implementation. The results of this study are that each student is able to receive new insights in using technology to learn responsibly and wants to be a smart student in using technology so that students at the Anugerah Tanjungpinang Social Service Foundation Middle School said that "it turns out that learning to use technology is so much fun and can make it easier for students to access learning resources quickly, students also get new things for example such as using devices such as Microsoft Word, Excel and so on. This is one form of success for the PkM team where students can understand and receive knowledge about the responsible use of technology.